(untitled) (Research, Society and Development, 2020)
Objective: To analyze scientific productions about the care provided by nursing professionals to cancer patients related to the prevention of pressure injuries. Methodology: This is an integrative literature review, with a qualitative approach carried out in the databases, via VHL, with a time frame from 2008 to 2018 and submitted to thematic analysis. Results: An incipience of productions about the theme was identified. Regarding the qualitative analysis, two thematic categories emerged: determining factors in the formation of pressure injuries in cancer patients and nursing care related to the prevention of pressure injury in cancer patients. Conclusion: The comorbidities of the cancer patient, depending on the disease or treatment, are linked to risk factors for the development of pressure injuries. Thus, the nurse must implement preventive actions, minimize risks, in addition to carrying out permanent education and guidance to patients and family members / companions, in care settings, in-hospital or home.